2021
DOI: 10.1016/j.diabres.2020.108529
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic retinopathy is independently associated with increased risk of intubation: A single centre cohort study of patients with diabetes hospitalised with COVID-19

Abstract: In our study of 187 patients with diabetes hospitalised with COVID-19 we observed a more than 5 fold increased risk of intubation in patients with diabetic retinopathy. Further studies are required to understand the mechanisms that explain the associations between retinopathy and other indices of microangiopathy with severe COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 7 publications
0
16
0
2
Order By: Relevance
“…Due to the nature of the study, causal link or underlying mechanism of the association was not established. However, authors speculated that diabetic microangiopathy could have been a surrogate marker of a preexisting endothelial dysfunction/damage which may represent a risk factor for an increased severity of respiratory dysfunction in COVID-19 [14].…”
Section: Diabetes Mellitus and Diabetic Retinopathymentioning
confidence: 99%
“…Due to the nature of the study, causal link or underlying mechanism of the association was not established. However, authors speculated that diabetic microangiopathy could have been a surrogate marker of a preexisting endothelial dysfunction/damage which may represent a risk factor for an increased severity of respiratory dysfunction in COVID-19 [14].…”
Section: Diabetes Mellitus and Diabetic Retinopathymentioning
confidence: 99%
“…Nessa mesma perspectiva analítica, Corcillo et al (2021), descrevem que ao comparar os pacientes intubados com os não intubados, os resultados foram semelhantes com menor idade, menor duração do diabetes e maior prevalência de retinopatia e obesidade. Além de não evidenciar associação significativa entre a intubação e outras variáveis de fatores qualitativos como o sexo, etnia, dentre outros fatores como o uso de bloqueadores do sistema reninaangiotensina-aldosterona, tipo de diabetes, hipertensão, função renal e nível de glicose no momento da admissão.…”
Section: Resultsunclassified
“…Only a few studies have investigated the effect of individual diabetic microvascular complications on COVID-19 outcomes. A single centre study of 189 hospitalised COVID-19 patients with diabetes ( Corcillo et al, 2020 ), identified that the presence of diabetic retinopathy was associated with over five-fold increased odds of intubation (OR 5.81, 95% CI 1.37–24.66 [ P < 0.001]), independent of other well-established COVID-19 risk factors. In the study, 80% of patients with retinopathy had background retinopathy.…”
Section: Microvascular Complications Of Diabetes As a Risk Factor For Severe Covid-19mentioning
confidence: 99%